2019
DOI: 10.1080/16506073.2019.1575900
|View full text |Cite
|
Sign up to set email alerts
|

Mental health training, attitudes toward support, and screening positive for mental disorders

Abstract: Public Safety Personnel (PSP; e.g. correctional workers, dispatchers, firefighters, paramedics, police) are frequently exposed to potentially traumatic events (PTEs). Several mental health training program categories (e.g. critical incident stress management (CISM), debriefing, peer support, psychoeducation, mental health first aid, Road to Mental Readiness [R2MR]) exist as efforts to minimize the impact of exposures, often using cognitive behavioral therapy model content, but with limited effectiveness resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
138
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(155 citation statements)
references
References 47 publications
13
138
0
4
Order By: Relevance
“…PSP and FHP are regularly exposed to PPTEs, such as threats, violence, accidents, fatalities, and suicide, as well as occupational stressors (e.g., shift work, public scrutiny, harassment or bullying) [ 1 , 2 , 3 , 5 , 6 ]. PTSIs resulting from PPTEs include symptoms of mood and anxiety disorders, as well as other mental disorders (e.g., PTSD), suicidal behaviors (i.e., ideation, planning, attempts), and maladaptive coping strategies (e.g., drug abuse, alcohol abuse, avoidance) [ 2 , 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PSP and FHP are regularly exposed to PPTEs, such as threats, violence, accidents, fatalities, and suicide, as well as occupational stressors (e.g., shift work, public scrutiny, harassment or bullying) [ 1 , 2 , 3 , 5 , 6 ]. PTSIs resulting from PPTEs include symptoms of mood and anxiety disorders, as well as other mental disorders (e.g., PTSD), suicidal behaviors (i.e., ideation, planning, attempts), and maladaptive coping strategies (e.g., drug abuse, alcohol abuse, avoidance) [ 2 , 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTSIs resulting from PPTEs include symptoms of mood and anxiety disorders, as well as other mental disorders (e.g., PTSD), suicidal behaviors (i.e., ideation, planning, attempts), and maladaptive coping strategies (e.g., drug abuse, alcohol abuse, avoidance) [ 2 , 6 , 7 , 8 ]. The impact of PTSIs may include a reduction in the quality of occupational performance, increased absenteeism, sleep difficulties, a negative impact on relationships with others, burnout, other physical or psychological illnesses, disability, and early mortality [ 5 , 41 , 42 , 43 ]. The economic burden of PTSIs within PSP and FHP in Canada remains unknown, but productivity losses that result from mental disorders experienced in the Canadian workforce are estimated to be anywhere between $16.6 billion [ 44 ] and $51 billion [ 45 , 46 , 47 ] annually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, responses were based on anonymous online self-reporting of current symptoms, making reliability and validity ambiguous [40]; however, the results are consistent with previous Canadian correctional worker responses and increased reliability and validity would require a substantial investment. Fourth, even when anonymous, people may underreport clinical symptoms [41,42], and PSP, including correctional workers, report substantial concerns regarding stigma and confidentiality [5,6,[43][44][45][46]. Fifth, even well-validated and conservative self-report screening tools are only approximations.…”
Section: Limitationsmentioning
confidence: 99%
“…Researchers recently revealed that PSP in general are reluctant to access formal care and that PSP with mental health training report somewhat higher levels of perceived access to care and willingness to access services [67,68]. Therefore, treatment and prevention approaches specifically tailored for PSP may be necessary.…”
Section: Discussionmentioning
confidence: 99%